Some less-known plants parts as supplementary foods - Sharma, P P; Savant, R J (International Multidisciplinary Research Journal, 2013)
Utilization of wild edible plants as a food source is an integral part of the culture of indigenous people that dwell in and nearby forests, who gather and consume wild edible plants as snacks, as a vegetable and at times of food scarcity. In India comparison of ethnobotanical knowledge between different regions and ethnic groups has been a major area of research done during last two decades. Present communication deals with the comparative ethnobotany of India and Africa. Over 750 species have been recorded as common to India and Africa. Of these, 14 plants which are reported as edible in African literature, but the part used in Africa seems to be less-known as edible in India, some examples of such plants and parts are Adensonia digitata (leaves and young roots), Balanites aegyptiaca (young leaves and shoots), Cleome gynandra (leaves and flower), Dactyloctenium agyptium (roots) and Grewia tenax (roots).